Some Late 4th-century Comic Fragments (Antiph. fr. 288 = Timocl. fr. 41 = adesp. tr. fr. 123a; Antiph. fr. 167; adesp. com. fr. 149) and Eratosthenes of Cyrene on Demosthenes - Olson, S. Douglas (Hyperboreus, 2019)
The seeming assignment of an iambic trimeter line (= adesp. tr. fr. 123 a) to Antiphanes (fr. 288) and Timocles (fr. 41) at Pseudo-Plutarch Lives of the Ten Orators 845 b, in the course of a brief description of Demosthenes’ early career, is actually a reference to Antiph. fr. 167. 2–3, on the one hand, and to adesp. com. fr. 149 (which ought to be assigned to Timocles), on the other. Antiph. fr. 288 = Timocl. fr. 41 should thus be regarded as dubia at best.